Teachers' humor and its relationships with chronic fatigue − the mediating role of the sense of stress at work - Agnieszka Kruczek (Nofer Institute of Occupational Medicine, 2019)
Background In recent years, many scientific studies, both in Poland and in the world, have proven that teaching is considered a profession with a high level of stress. The experience of prolonged stress and a lack of abilities to meet challenges can lead to the occurrence of chronic fatigue in teachers. Of key importance in coping with stress are personal resources, which include humor described by humor styles and coping humor. Material and Methods The study involved 166 teachers (145 women and 21 men) aged 23-67 (M = 43.02, SD = 9.98). The following tools were used in the research: the Coping Humor Scale (CHS), the Humor Style Questionnaire (HSQ), the Sense of Stress at Work (PSS-10P) (the Polish modification of the 10-item Perceived Stress Scale - PSS-10), the Checklist Individual Strength (CIS20R) and a personal questionnaire. Results In the light of the research, teachers were characterized by a medium level of the sense of stress at work, coping humor and chronic fatigue. Affiliative and self-enhancing styles dominated in this group. The more often teachers used the affiliative and self-enhancing styles, the less likely they were to experience chronic fatigue. The sense of stress at work mediated the relationship between the positive dimensions of humor and chronic fatigue and its dimensions. In contrast, aggressive and self-deprecating humor styles were not associated with chronic fatigue. Conclusions It can be hypothesized that positive humor protects against chronic fatigue. The sense of stress at work plays an important role in explaining this relationship. Med Pr. 2019;70(3):343-61